Trends in "Green" Design - making ground source heat pumps the system of choice - Hasler, Fred L. (Kansas State University, 2008)
Ground source heat pump systems have been around for nearly 50 years. The efficiencies that can be achieved today are difficult to match with any other type of heating and air conditioning system. With the familiarity of the system, installed costs have become very reasonable, and in some cases have been the same or less expensive than other comparable systems. Given all this, the question remains – why aren't more of these systems being proposed and installed? This report will investigate some of the reasons why and what can be done to remedy them. Major issues include professional education, availability of research and design material, industry or governmental incentives, and education in our K-12 schools and universities. Certainly all participants in the design process, from the designer to the owner, play a part in this dilemma. Recommendations will be made that address key hurdles this industry faces regarding making ground source heat pumps the system of choice.
Keywords: Green Design; Heating and Cooling Systems; Engineering, General (0537)